A mathematical framework for curved active constrained layer structures: well-posedness and approximation1. (December 2019) - Banks, H.T.; Medhin, N.G.; Zhang, Y.
Abstract : We present a mathematical framewirk to provide general well-posedness and approximation results for a class of models for piezoceramic activated constrained layer structures. The models include unbounded inputs from the piezo material and hysteresis in the viscoelastic constrained layers, and describe coupled bending and longitudinal vibrations in curved structural members. Families of linear/cubic splines are used to illustrate the approximation ideas.